2021
DOI: 10.1038/s41467-021-27334-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a fluorescent chemogenetic reporter with tunable color for advanced live-cell imaging

Abstract: Biocompatible fluorescent reporters with spectral properties spanning the entire visible spectrum are indispensable tools for imaging the biochemistry of living cells and organisms in real time. Here, we report the engineering of a fluorescent chemogenetic reporter with tunable optical and spectral properties. A collection of fluorogenic chromophores with various electronic properties enables to generate bimolecular fluorescent assemblies that cover the visible spectrum from blue to red using a single protein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 63 publications
2
73
0
Order By: Relevance
“…It was originally proposed that the chromophore adopts in FAST a quasi-planar conformation with an orientation of the phenolic ring that enables Glu46 to stabilize the anionic phenolate state (Figure a), explaining both the high fluorescence quantum yield and the red-shifted absorption. This mode of binding was recently confirmed independently by the determination of the structure of FAST by nuclear magnetic resonance and the in silico modeling of FAST variants bound to various fluorogens . The unique fluorogenicity mechanism involving both quantum yield increase through conformational locking and absorption red-shift through protonation enables to minimize fluorescence background that could result from potential off-target interactions.…”
Section: Prototypical Fastmentioning
confidence: 75%
See 1 more Smart Citation
“…It was originally proposed that the chromophore adopts in FAST a quasi-planar conformation with an orientation of the phenolic ring that enables Glu46 to stabilize the anionic phenolate state (Figure a), explaining both the high fluorescence quantum yield and the red-shifted absorption. This mode of binding was recently confirmed independently by the determination of the structure of FAST by nuclear magnetic resonance and the in silico modeling of FAST variants bound to various fluorogens . The unique fluorogenicity mechanism involving both quantum yield increase through conformational locking and absorption red-shift through protonation enables to minimize fluorescence background that could result from potential off-target interactions.…”
Section: Prototypical Fastmentioning
confidence: 75%
“…This mode of binding was recently confirmed independently by the determination of the structure of FAST by nuclear magnetic resonance 14 and the in silico modeling of FAST variants bound to various fluorogens. 2 The unique fluorogenicity mechanism involving both quantum yield increase through conformational locking and absorption red-shift through protonation enables to minimize fluorescence background that could result from potential off-target interactions. Molecular engineering studies showed that varying the substituents on the aromatic ring of the fluorogen could generate various spectral properties in the green to red region 15 (Figure 3).…”
Section: ■ Prototypical Fastmentioning
confidence: 99%
“…Next to iFAST and nanoFAST, also far-red FAST (frFAST), redFAST and greenFAST were developed, permitting far-red, orange-red and green fluorescence readouts, respectively (Table 2) [73,74]. Remarkably, promiscuous FAST (pFAST) was designed displaying the ability to cover the entire visible spectrum as a result of its capacity to bind various fluorogenic chromophores, each resulting in different fluorescence readouts (Table 2) [75].…”
Section: Fast a New Fluorescent Reporter Allowing Real-time Monitorin...mentioning
confidence: 99%
“…1d) demonstrated that HBR-3,4,5TOM could enter the binding cavity of the FAST and be stabilized by the hydrogen bond with T98 as well as apolar interactions with I31, F62, V66, A67, T70, I96, P97 and V122. However, the hydrogen-bond network formed by the conserved residues Y42 and E46 to stabilize the phenolate anion 36,37 in the O-FAST disappeared in the FAST:HBR-3,4,5TOM complex, potentially resulting in a decrease in affinity. Taken together, modifying the hydroxyl group of the ligand could diminish its binding with the FAST and efficiently reduce the complex uorescence.…”
Section: Design Principle Of the Srfast Platformmentioning
confidence: 99%